Developing academic literacy through a decentralised model of English language provision. Issue 10 (26th November 2019) - Murray, Neil; Muller, Amanda
ABSTRACT: Students entering English-medium universities frequently struggle to cope with the language demands of their degree programmes, despite having met the English language entry conditions stipulated by their receiving institutions. This can have significant repercussions for the teaching-learning process, for the student experience and for universities' reputations. Most universities, therefore, have in place some form of in-sessional English language support to develop students' language proficiency. Such provision tends to be centralised and to offer English for general academic purposes rather than language development that responds in a more nuanced way to the particular literacy needs of students' disciplines. In this article we report on an alternative, decentralised model of language support, implemented in a School of Nursing and Midwifery, and which seeks to develop students' competency in the language skills required for their Nursing studies and professional practice. Results to date have been encouraging and provide further evidence that such tailored provision offers a potentially fruitful language development strategy.